2019
DOI: 10.1002/jcop.22156
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the ecological context of mental, emotional, and behavioral health problems: A person‐centered approach

Abstract: Aims: The social/environmental context of youth is important for mental, emotional, and behavioral (MEB) health. This study used person‐oriented methods to examine the influences of family, neighborhood, and poverty on late adolescent MEB outcomes. Methods: Latent class analysis was used to discern significant clusters of at‐risk, diverse young men (N = 625) based on contextual factors; differences in MEB outcomes were examined. Results: Four classes emerged. Resourced and Protected youth had low risk across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…Given that both profiles included almost average levels of monitoring, the level of caregiver warmth appears to be especially crucial to adolescent mental health. This aligns, to some extent, with pre-existing studies that have reported that higher caregiver warmth is associated with better adolescent outcomes (Baumrind, 2005;Logan et al, 2019;Rothenberg et al, 2020a, b, c), also in South African samples of HIV-infected or -affected adolescents (Bhana et al, 2016;Boyes et al, 2019;Casale et al, 2015;Sharer et al, 2015;Shenderovich et al, 2021). Still, none of these prior studies investigated warmth and monitoring combinations and their complex relationships with the mental health of younger and older male and female adolescents.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Given that both profiles included almost average levels of monitoring, the level of caregiver warmth appears to be especially crucial to adolescent mental health. This aligns, to some extent, with pre-existing studies that have reported that higher caregiver warmth is associated with better adolescent outcomes (Baumrind, 2005;Logan et al, 2019;Rothenberg et al, 2020a, b, c), also in South African samples of HIV-infected or -affected adolescents (Bhana et al, 2016;Boyes et al, 2019;Casale et al, 2015;Sharer et al, 2015;Shenderovich et al, 2021). Still, none of these prior studies investigated warmth and monitoring combinations and their complex relationships with the mental health of younger and older male and female adolescents.…”
Section: Discussionsupporting
confidence: 79%
“…Still, caregiver warmth was above average in the second profile (Substantial Caregiver Warmth and Some Monitoring profile), and it was higher than caregiver monitoring. The fact that most of the sample (i.e., 83.61%) reported above average levels of caregiver warmth discourages a priori assumptions that warm caregiving is unlikely in disadvantaged communities (Logan et al, 2019). Instead, it urges attention to the resilience of these stress-exposed caregivers, with special emphasis on better understanding and better supporting the resources that informed their continued capacity to parent positively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations